2019
DOI: 10.1002/ajp.23053
|View full text |Cite
|
Sign up to set email alerts
|

Primate microbial endocrinology: An uncharted frontier

Abstract: Gut microbial communities communicate bidirectionally with the brain through endocrine, immune, and neural signaling, influencing the physiology and behavior of hosts. The emerging field of microbial endocrinology offers innovative perspectives and methods to analyze host-microbe relationships with relevance to primate ecology, evolution, and conservation. Herein we briefly summarize key findings from microbial endocrinology and explore how applications of a similar framework could inform our understanding of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Hypothetical models of host-microbiome interaction point out that environmental and host-related factors work in concert to sculpt bacterial communities in wild primates (Amato and Righini, 2015;Benavidez et al, 2019). Supporting this notion, here we showed that gut bacterial communities of black howler monkeys living in disturbed forest fragments could be influenced not only by food availability (as a surrogate of diet), which is a significant ecological factor contributing to shape wildlife microbiomes, but also by the host endocrine physiology.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Hypothetical models of host-microbiome interaction point out that environmental and host-related factors work in concert to sculpt bacterial communities in wild primates (Amato and Righini, 2015;Benavidez et al, 2019). Supporting this notion, here we showed that gut bacterial communities of black howler monkeys living in disturbed forest fragments could be influenced not only by food availability (as a surrogate of diet), which is a significant ecological factor contributing to shape wildlife microbiomes, but also by the host endocrine physiology.…”
Section: Discussionsupporting
confidence: 77%
“…Studies investigating the interplay between stress reactions and the gut microbiome in wildlife are still limited, but an emerging field exploring the communication between endocrine and gut microbiome systems in free ranging animals is currently developing (see Benavidez et al, 2019). Stress responses may induce intestinal disorders affecting microbial structure and/or metabolism in wild and domestic animals (Söderholm et al, 2002;Li et al, 2018;Yan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, microbiome time-series data sets that include hormone information, such as those that measure metabolites of steroid hormones in fecal samples, 56 , 57 will be particularly valuable for parsing out a second potential mechanism of lifetime microbial stability. Glucocorticoids have a pervasive genetic component, 58–60 and a study on primate microbial endocrinology 61 proposes that host–microbiome signaling via the endocrine system may promote microbiome stability. This suggests that one potential mechanism for the host genetic influence on microbial stability is via glucocorticoid levels.…”
Section: How Time Series Data Can Inform Host Genetics Effects On The...mentioning
confidence: 99%
“…Microorganisms can not only respond to eukaryotic signal molecules, but also express a variety of host HRF, for example, during stress. As a result, a new field of microbial endocrinology has emerged, which studies the bidirectional mechanisms of signaling interaction between the microbiota and humans [ 8 , 9 ]. Undeniable evidence shows that a microorganism’s signal molecules play a significant role in the regulation of the endocrine, immune, vegetative, intestinal, and nervous systems of humans and animals.…”
Section: Introductionmentioning
confidence: 99%